(untitled) (Revista Contexto & Saúde, 2023)
Background: The meditation can be a strategy for coping with psycho-emotional and physical comorbidities, that affect people living with HIV (PLWH), and that can be exacerbated in Covid-19 pandemic. Aim: To evaluate the levels of TCD4+ and TCD8+ cells, viral load, and metabolic parameters of PLWH submitted to meditation sessions. Experimental procedure: Case-crossover study in which 07 (seven) participants attended guided meditation sessions remotely, between July and August 2020 (8 weeks), one session per week, with an average duration of 1h each. Quantification of TCD4+ and TCD8+ lymphocytes was performed by flow cytometry; the viral load was detected by the polymerase chain reaction technique and the metabolic parameters by chemiluminescence. Results: Meditation kept the levels of TCD4+ (p=0.93) and TCD8+ (p=0.37) and viral load (<40) lymphocytes constant. Was observed an increase in high density lipoprotein-cholesterol (HDL-c) (p=0.01*), however glucose (p=0.15), triglycerides (p=0.43), total cholesterol (p=0.18), Glutamic Oxaloacetic Transaminase (p=0.46) and Glutamic Pyruvic Transaminase (p= 0.36) did not change. Conclusion: Meditation increases HDL-c in PLWH. The TCD4+ and TCD8+ lymphocyte levels and viral load remained constant during the intervention. The adherence to application of meditation can translate into a greater commitment to the search for health, and thus, improve the quality of life of these individuals.